Implementation of Material-Based Inquiry to Improve the Critical Thinking Ability of Senior High School Students - Nofriza, Elvitri; Rery, Usman; Noer, Asmadi M (FKIP-Universitas Riau, 2020)
The development of technology today has a huge impact on education, especially in the learning process. Therefore, an educator must be able to adapt the learning process to technological developments. One way to apply technology development in learning systems is to use e-modules in the learning process. The purpose of this study is to use guided inquiry-based e-modules to see the magnitude of the increase in students' critical thinking skills in the material reaction rate after using guided inquiry-based e-modules. The research method used a quasy experiment with a pretest-postest design using two classes as the experimental class and the control class. The sample in this study were students of State Senior High School (SMAN) 1 Sebrida Indragiri Hulu class XI. The results obtained were an increase in students' critical thinking abilities from before the use of guided inquiry-based e-modules. After the use of e-module based guided inquiry. This increase is seen from the comparison between the experimental class and the control cash class. The experimental class using e-module has a higher critical thinking ability of students than the control class that does not use e-module in the learning process.